Bisferrocenyl-functionalized pseudopeptides: access to separated ionic and electronic contributions for electrochemical anion sensing. Issue 42 (11th April 2016) - Pandey, Mrituanjay D.; Martí-Centelles, Vicente; Burguete, M. Isabel; Montoya, Noemí; Luis, Santiago V.; García-España, Enrique; Doménech-Carbó, Antonio
Abstract : Pseudopeptidic receptors containing ferrocene fragments have been prepared and their response to a series of anions was measured by a voltammetry of microparticles methodology. Abstract : Pseudopeptidic receptors containing ferrocene fragments have been prepared and their response to a series of anions was measured by a voltammetry of microparticles methodology. Such water-insoluble compounds yield anion-assisted reversible solid-state oxidations differing in their open-circuit potential and their midpeak potential recorded in cyclic voltammetric measurements. The difference between those potentials provides the individual thermodynamic contributions of electron and proton transfer, revealing that the mechanism of an ion-sensitive electrode can differ in potentiometry and voltammetry. The studied receptors are potentially interesting for potentiometric sensing, showing relatively high selectivity for H2 PO4 − and HPO4 2− anions.